Integración regional de la Educación Superior. El espacio Iberoamericano del conocimiento y el papel pedagógico de la Organización de Estados Iberoamericanos - José Antonio Ramírez Díaz (EccoS – Revista Científica)
This paper discusses strategies for the transfer of policies of international organizations to countries in Latin America. We review the role of the Organization of American States and the Latin American Summit in the production of policies for the integration of higher education in the region to relieve the circuit which is generated by regional policies. At the end of the work is a reflection of the commercial dimension implicit in educational change, which, lets assume that the Summit is not just a space to carry out a project of regional cooperation but also contribute in the development of interest Spanish economic.